1967
DOI: 10.1083/jcb.34.3.801
|View full text |Cite
|
Sign up to set email alerts
|

Tubular and Fibrillar Components of Mature and Differentiating Sieve Elements

Abstract: An ontogenetic study of the sieve element protoplast of Nicotiana tabacum L. by light and electron microscopy has shown that the P-protein component (slime) arises as small groups of tubules in the cytoplasm. These subsequently enlarge to form comparatively large compact masses of 231 2.5 (SE)A (n = 121) tubules, the P-protein bodies. During subsequent differentiation of the sieve element, the P-protein body disaggregates and the tubules become dispersed throughout the cell. This disaggregation occurs at about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
0
1

Year Published

1969
1969
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(40 citation statements)
references
References 19 publications
3
36
0
1
Order By: Relevance
“…2). In immature tobacco sieve elements, P-protein maturation is characterized by the formation of large protein bodies (5,10), and similar fluorescent protein complexes were identified in the transgenic lines. The most striking demonstration of P-protein-like activity was the behavior of the NtSEO fusions after wounding: The fluorescent complexes in wounded transgenic plants formed distinctive plugs on most sieve plates, and these plugs sometimes even terminated with gel-like transcellular strands, as is consistent with the known characteristics of P-proteins (47,48).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2). In immature tobacco sieve elements, P-protein maturation is characterized by the formation of large protein bodies (5,10), and similar fluorescent protein complexes were identified in the transgenic lines. The most striking demonstration of P-protein-like activity was the behavior of the NtSEO fusions after wounding: The fluorescent complexes in wounded transgenic plants formed distinctive plugs on most sieve plates, and these plugs sometimes even terminated with gel-like transcellular strands, as is consistent with the known characteristics of P-proteins (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…1 and Fig. S2) mirrored the rapid assembly of conventional P-protein bodies in immature phloem cells (5). Furthermore, the expression of NtSEO genes as hrGFP fusions in a homologous genetic background resulted in the assembly of fluorescent proteinaceous agglomerates that reflected the characteristic morphology of structural P-proteins (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Srivastava and O'Brien (1966b) reported small fibrils in sieve cells of secondary phloem in the trunks of pine and suggested that they may have had a plastid origin. The fibrils found in the sieve cells of pine leaves are much smaller (5-7 nm) than the 23.1-H-9 nm diameters reported for P-protein in some angiosperms (Cronshaw and Esau, 1967). However, in Coleus the P-protein tubules (20 nm) are converted to 7 nm fibrils (Steer and Newcomb, 1969).…”
Section: Discussionmentioning
confidence: 96%
“…Chez le tabac, la future cellule criblée possède un seul et volumineux corps muqueux. Ce dernier est constitué de tubules protéiques dont le diamètre est d'environ 230 Â : il s'agit de protéine-Pl (Cronshaw et Esau, 1967Esau, et 1968.…”
unclassified